Social support and its relationship to psychological well-being among tenth grade students in the governorates of Gaza - Al-Kayal, Doaa Salim Ali (Journal of Educational and Psychological Sciences, 2023)
The study aimed to identify social support and its relationship to psychological well-being among tenth grade students in the governorates of Gaza, identify the level of social support among tenth grade students, identify the level of psychological well-being among tenth grade students, and reveal the existence of a statistically significant relationship between social support and psychological well-being among the tenth grade students, and the detection of statistically significant differences in the average scores of the sample members on the scale of social support and psychological well-being in the light of a variable (gender - economic level - directorate). The researcher used the descriptive analytical method, and the study sample consisted of (288) students The tenth grade for the year 2021/2022 AD, and they were selected by random sampling method, and the study reached the following results: The level of social support is (69.9%), which is a high level, and the relative weight of psychological well-being reached (73.9%), which is a high level, as it is clear that there is no Differences between the average responses of the respondents about social support according to each of the variables of gender, economic level, directorate and all dimensions, as it is clear that there are no differences between the average response of respondents On welfare according to each of the variables: gender, economic level, and district. For all dimensions, the researcher recommended, in light of the results, the following: the need to give the school full attention to students, and the need to hold workshops for teachers to urge them to use social support and its relationship to psychological well-being towards students.
Keywords: social support; psychological well -being; tenth grade students; Gaza governorates